Association between energy-adjusted dietary inflammatory index and sleep quality disorders: a cross-sectional study on fasa adult cohort - Sina Bazmi; Hossein Pourmontaseri; Seyede Fateme Mousavi Shahraki; Ahmad Reza Pourmontaseri; Alireza Askari; Pezhman Bagheri; Reza Homayounfar; Mojtaba Farjam; Azizallah Dehghan; Bahareh Fakhraei; Farhad Vahid; Nematollah Jaafari (Journal of Health, Population and Nutrition)
Abstract Background The cross-link between diet, sleep quality, and chronic inflammation is increasingly recognized and gaining significant attention. However, current research on this topic is limited and conflicting. In this study, we explore the connection between diet’s inflammatory potential, measured by the Energy-Adjusted Dietary Inflammatory Index (E-DII), and sleep disorders in a rural Iranian population. Our hypothesis suggests that an inflammatory diet may contribute to sleep quality disorders. Methods This cross-sectional study included data from the Fasa Adult Cohort Study (FACS) (n = 10,138). Sleep efficiency < 85%, sleep duration < 7 h, and sleep latency > 15 min were defined using the Pittsburgh Sleep Quality Index (PSQI). The E-DII was calculated using a validated 125-item food frequency questionnaire. Multivariable logistic regression models assessed the association between E-DII quartiles and sleep disorders. Results Our analyses included 9,761 individuals with a mean age of 49 ± 10 years. The average E-DII was − 0.30 ± 2.05. After adjusting for several confounders, participants in the highest quartile of E-DII had significantly higher odds of experiencing high sleep latency (OR = 1.30, 95%CI: 1.11–1.51, p-value < 0.001), low sleep efficiency (OR = 1.43, 95%CI: 1.17–1.76, p-value < 0.001), using sleeping pills (OR = 1.53, 95%CI: 1.19–1.97, p-value < 0.001), and no leg restlessness (OR = 0.83, 95%CI: 0.71–0.97, p-value 0.02) compared to those in the lowest quartile. However, E-DII did not correlate with sleep duration or daily dozing-offs. Conclusion Our findings have implications for dietary interventions in managing sleep disorders. Individuals with sleep difficulties, particularly in initiating sleep, are advised to reduce intake of proinflammatory nutrients and increase consumption of anti-inflammatory nutrients.